Internalisasi Moderasi Beragama melalui Literasi Digital dalam Pembelajaran PAI-BP Era Society 5.0 - Gilang Andriansyah; Antiti Armilah; Miftah Imam Sauqi; Aditya Budi Pratama; Akhsin Ridho (Halaqa: Journal of Islamic Education, 2026)
This research aims to analyze the process of internalizing religious moderation through digital literacy in Islamic Religious Education and Character Building (PAI-BP) learning. A qualitative approach with a case study design was employed at SMPN 1 Tengahtani, involving two PAI-BP teachers and five students as participants. Data were collected through observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The results indicate that the internalization of religious moderation is implemented through the use of Google Classroom, Wayground interactive quizzes, and creative digital projects. The findings reveal that the internalization process occurs through four main stages: content exposure, critical reflection, content production, and habituation of tolerant interaction. The novelty of this research lies in the formulation of a pedagogical framework for internalizing religious moderation based on digital literacy that prioritizes strengthening students' critical abilities. The implication of this study emphasizes that PAI-BP learning must equip students with epistemological skills to filter religious information on social media to maintain a moderate attitude in cyberspace.